PENGARUH PELATIHAN, DISIPLIN KERJA,PENGEMBANGAN KARIR, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DI KLINIK SILIWANGI CIMAHI - Laskawina; Setiawan, Joko (ITB AAS Indonesia Surakarta, 2025)
This study was conducted at Siliwangi Clinic in Cimahi to analyze the factors influencing employee performance, including training, work discipline, career development, and leadership style. The clinic faces several issues, such as difficulty in attending professional training due to a tight service schedule, low employee discipline (e.g., frequent tardiness and inappropriate work attire), lack of transparency in career development, and weak leadership presence and enforcement. The objectives of this research problem: (1) to analyze the influence of the relationship between training and employee performance at the Siliwangi Clinic, Cimahi, (2) to analyze the influence of work discipline on employee performance at the Siliwangi Clinic, Cimahi, (3) to analyze the influence of the relationship between career development and employee performance at the Siliwangi Clinic, Cimahi, (4) to analyze the influence of the relationship between leadership style and employee performance at the Siliwangi Clinic, Cimahi, (5) to analyze the influence of the relationship between training, work discipline, career development and leadership style on employee performance at the Siliwangi Clinic, Cimahi. The population of this study was 47 employees. Data collection techniques were questionnaires and interviews. The research method used the Multiple Linear Regression model. The research findings indicate that: Training (X1) has a significant effect on employee performance (Y) with a coefficient of 0.298. Work discipline (X2) also has a significant effect on employee performance (Y) with a coefficient of 0.250. Career development (X3) has no significant effect on employee performance (Y) with a coefficient of 0.045. Leadership style (X4) has a significant effect on employee performance (Y) with a coefficient of 0.52. Simultaneously, all four variables have a significant effect on employee performance, as shown by F-value of 24.348, which is greater than the F-table value of 2.588.